Classroom Activities in Content and Language Integrated Learning - Evi Puspitasari (Universitas Muhammadiyah Yogyakarta, 2016)
AbstractContent and Language Integrated Learning is an approach used to teach subjects which focus on learning a new language and content. This approach is usually implemented to teach content through a target language. In an English training program in Indonesia, this approach is applied by using English as a medium of instruction to teach concepts and theory-based subjects. Since the students should accomplish the target language and concepts of pedagogy, they need activities to assist them in the dual-focused process. This research is going to scrutinize what activities are implemented in the program to achieve the learning goal. By interviewing four sophomore students who enrolled two content subjects in semester three, the data were gained. Four classroom activities used were revealed. Those were quiz, group presentation, group teaching and classroom discussion. Students’ responses toward each activity were good. However, some notes regarding teachers’ decision and roles were addressed. It proved a teacher is a factor that brings the CLIL activities into success or failure. Keywords: Content and Language Integrated Learning, CLIL, classroom activities, students’ responses